First snapshot comparison of nephrotoxic potentials of four common organic UV filters in juvenile and adult zebrafish (Danio rerio) - Ba Reum Kwon; Gowoon Lee; Inae Lee; Ah-Reum Jo; Jeonghwan Lee; Na-Youn Park; Younglim Kho; Jung Pyo Lee; Kyungho Choi (Journal of Hazardous Materials Letters)
To protect against UV light, organic UV filters (UVFs) are widely used in sunscreen and various consumer products. Concerns regarding the potential health impacts of UVFs have been raised, however, information is mostly limited to their endocrine disruptions. The present study aims to investigate nephrotoxic potentials of four major organic UVFs, i.e., avobenzone (AVB), benzophenone-3 (BP-3), octocrylene (OC), and octyl methoxycinnamate (OMC), using a zebrafish model at different life stages. Test UVFs were applied during early (0–30 days post-fertilization (dpf)), and adult life stage (> 6 months old, 21 d exposure), and investigated for alterations in gene expression and/or kidney function. In juvenile fish (30 dpf), early life stage exposure to BP-3 and OMC caused significant induction of proteinuria. Moreover, regardless of life stage, key genes (wt1a, podocin, nephrin, cdh17, sim1a, and kim-1) responsible for kidney structure and function showed transcriptional alterations that support nephrotoxic potentials of the test UVFs. Our results demonstrate that exposure to widely used organic UVFs could impair normal biological processes for maintaining kidney health during both life stages. Considering the widespread use of organic UVFs among the general human population, the implication of this nephrotoxic potential warrants further investigation.